Improving the quality of primary ESL teachers' shared reading practice : a collaborative action research - Satirah, Ahmad (2017)
Shared reading is an excellent strategy to enhance reading literacy in both first and second language learning context but has not been effectively utilised by teachers in Malaysian primary ESL classrooms. This collaborative action research aimed to support two English teachers’ implementation of shared reading through four continuous and recursive spirals. A Systematic Assessment of Book Reading (SABR) by Zucker et.al (2010) was used to examine teachers’ existing shared reading practice during the first cycle. The modified version of SABR called the Systematic Assessment of Second Language Book Reading (SABRL2) was used to guide teachers to conduct second language shared reading during the three subsequent cycles. The tool consists of seven constructs which are: 1) materials selection, 2) classroom physical arrangement, 3) language development, 4) abstract thinking, 5) elaboration, 6) selective use of the first language, and 7) session climate. Data were collected through interviews, team reflections, classroom observations, and reflective journal. Patterns were identified through a process of data familiarisation, data coding, and theme development using the computer-aided qualitative data analysis software Atlas.ti. Findings for the first cycle showed that the teachers have an inaccurate understanding of the principles of shared reading and their instructional behaviour did not promote higher order reading skills among pupils. The teachers also rarely created a warm and supportive setting for shared reading and tended to dominate the discussion during text related conversation. The first language (Malay Language) was also used excessively throughout the shared reading sessions. However, the teachers’ understanding and nature of instructional behaviour developed significantly due to guidance received using the SABRL2. This study suggests that SABRL2 can be used to help teachers increase the quality of reading literacy lessons in the ESL classroom and a collaborative action research can bring about changes in the classroom by giving teachers greater breadth and depth in understanding their own pedagogical practice.